Use your head - Buzan, Tony. (London : BBC, 2003)
Since 1974, Tony Buzan's manual on how to use the human brain has been translated into more than 20 languages. The book presents a range of techniques that are all designed to teach the reader how to think properly.
Previous ed.: 1995.
Includes bibliographical references (p. 155-156) and index.
Keywords: Intellect; Thought and thinking; Mental discipline; Psychology